Kebijakan Pemerintah tentang Penjaminan Mutu Pendidikan Islam - Muhammad Adhim Habibullah; M. Yahya Ashari (Lembaga Yasin AlSys, 2026)
Government policy on Islamic education quality assurance is a strategic instrument for ensuring the quality of Islamic educational institutions amid the challenges of globalization, social dynamics, and demands for public accountability. However, various studies indicate that the implementation of quality assurance policies in Islamic educational institutions still faces obstacles related to policy comprehension, human resource readiness, and the internalization of a quality culture. This study aimed to analyze government policy on Islamic education quality assurance and its contribution to improving the quality of Islamic educational institutions. It employed a library research method by reviewing books, policy documents, and relevant scholarly journal articles published in the last five years, while the data were analyzed using content analysis to identify key themes related to policies and practices of Islamic education quality assurance. The findings show that government policy has provided a clear normative framework through the Standar Nasional Pendidikan (National Education Standards) as well as internal and external quality assurance systems, which play an important role in encouraging Islamic educational institutions to undertake continuous planning, evaluation, and quality improvement. Nevertheless, policy implementation still exhibits variation across institutions, influenced by institutional and resource-related factors. This study concludes that Islamic education quality assurance policy makes a significant contribution to strengthening quality governance but still requires reinforcement at the implementation level; its implications underscore the urgency of developing human resource capacity and adopting more contextual policy approaches so that Islamic education quality assurance can be implemented effectively and sustainably.